The Implementation of Blended Learning in Social Studies Learning for 21st Century Skills Enhancement - Martanto, Siswo Dwi; Pramono, Suwito Eko; Sanjoto, Tjaturrahono Budi (Universitas Negeri Semarang, 2021)
Face-to-face conventional learning is less attractive, while online learning is also less effective. In the digital era of the 21st century, learning methods must follow the development of information technology under students' experiences, needs, interests, and learning styles. This study aimed to determine the implementation and effectiveness of blended learning in social studies learning to improve 21st-century skills. This study used a qualitative approach with a phenomenological design. Data collection techniques using observation, interviews, and documentation studies. The results showed that the implementation of blended learning in SMP Semesta Bilingual Boarding School Semarang was based on Google Classroom and Edunav with Chromebook, Microsoft Surface, and interactive digital smartboard. Implementing blended learning is effective for improving 21st-century skills because it follows today's students' characteristics, learning styles, and learning needs. Blended learning is the best solution for 21st-century social studies learning. Blended learning in social studies learning at SMP Semesta Bilingual Boarding School Semarang is a perfect blend of teachers, students, and 21st-century technology called Technology Integrated Classroom.